Spectroscopic assessment of heavy metals pollution in roadside soil and road dust: a review. Issue 7 (9th August 2021) - Maeaba, Wilson; Kumari, Rashmi; Prasad, Surendra
Abstract: Over the past few decades, heavy metal pollution has become a severe problem in many parts of the world as their concentrations are increasing at an alarming rate due to increasing unplanned industrialization and urbanization. In addition, road dust and roadside soils are threat to environmental quality as being one of the sources of the particulate matters that contain heavy metals from different sources. In order to understand the prominence, ecological and human health risks of heavy metals pollution in different compartments of the environment it has been essential to assess their concentrations, especially in road dust and roadside soil and attempted by different research groups in the world. The present review discusses briefly about road dust and roadside soil and various spectroscopic analytical techniques used for determination of heavy metals. From an environmental scope, it presents the occurrence of heavy metals like Pb, Cd, Cu, Cr, Ni, Zn, Fe and Co. This review presents significant work done on road dust and roadside soil in different cities in the world as global data and in Fiji, and their comparison as global data on assessment of heavy metals in road dust in the last few years.